Children of the Earth. 1, no.4 (Samhain, 1981) - (:unkn) unknown (Children of the Earth, 1981)
From the Dining Room Table / by Hestia -- [Neopagan Girl] / art by Jenny, 8 -- Letters -- Advertisement: Church of Seven Arrow -- Changes [of address] -- Notes from the Broomcloset: Thank you Goddess [prayer] ; But What Can I Teach my Kids / by Cloud -- NeoNatal Notes: Breastfeeding Facts Everyone Should Know / by Robin -- Parenting the Child Within / by Dana -- Unfinished Fable on the Responsibility of Dreams and Wishes / by Arwen Fae -- Kids In & Out of Circles / by Hilary -- Witch / art by Arne (age 4) -- Witch / art by Jenny (8) -- Pumpkin Ritual: a Family Affair / by Robin -- Pumpkin / art by Arne, age 4 -- Recipes: Pumpkin Pie ; Gourmet Pumpkin -- Jack-O-Lanterns / art by Jenny (8) -- A Gift of Light for Yule / by Cloud -- Solstice Fun / by Robin -- The Lorax by Dr. Seuss / review fby Filisis -- A Teacher's Minutes / poem by Filisis -- Selene by Z. Budapest / Review by Kimberly Mueller, age 8 -- Selene Cernunnos Friends Forever / art by Kimberly Mueller, age 8 -- Thank the Goddess / by Sonja (12) -- From North to South / by Angel, (13) -- The Dumb Dragon / short story by Kimberly Mueller, Age 8
1 Electronic record(s). 18647154 bytes. 26 pages. CotE_v01n04_1981.pdf
Keywords: Children of the Earth (Newsletter); Child artists; Home schooling--Religious aspects--Neopaganism; Critical thinking--Religious aspects--Neopaganism; Neopagan families; Child rearing--Religious aspects--Neopaganism; Child rearing--Religious aspects--Wicca; Patriarchy; Yule (Festival)--Prayers and devotions; Neopaganism--Prayers and devotions; Breastfeeding; Self-perception; Personal transformation; Wishes--Juvenile fiction; Wicca--Rituals--Child participation; Witches--Art; Food craft; Pumpkin carving; Jack-o-lanterns; Jack-o-lanterns--Art; Pumpkin pie--Recipes; Pumpkins--Recipes; Candle holders--Design and construction; Candlemaking; Bread dough craft; Handicraft for children; Seuss, Dr. Lorax; Budapest, Zsuzsanna Emese, 1940- Selene; Recipes; Reviews; Children's literature; Children's writings; Newsletters